2010
DOI: 10.1111/j.1460-9568.2010.07286.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylyl cyclase‐activating polypeptide controls the proliferation of retinal progenitor cells through downregulation of cyclin D1

Abstract: During retinal development, cell proliferation and exit from the cell cycle must be precisely regulated to ensure the generation of the appropriate numbers and proportions of the various retinal cell types. Previously, we showed that pituitary adenylyl cyclase-activating polypeptide (PACAP) exerts a neuroprotective effect in the developing retina of rats, through the cAMP-cAMP-dependent protein kinase (protein kinase A) (PKA) pathway. Here, we show that PACAP also regulates the proliferation of retinal progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 64 publications
(131 reference statements)
1
30
0
Order By: Relevance
“…15 Among the PAC1 receptor isoforms, the presence of Hop1 transcript has been reported in adult rat retina only, 30 and no quantitative data are available from newborn or developing tissue. In the present study, we not only demonstrated the presence of PAC1 receptors in different developmental stages of the postnatal rat retina but we showed that for quantification of PAC1 receptor expression, the existence of PAC1 receptor isoforms must be taken into account.…”
Section: Dynamic Changes Of Pac1 Receptor Isoforms Through Postnatal mentioning
confidence: 99%
See 2 more Smart Citations
“…15 Among the PAC1 receptor isoforms, the presence of Hop1 transcript has been reported in adult rat retina only, 30 and no quantitative data are available from newborn or developing tissue. In the present study, we not only demonstrated the presence of PAC1 receptors in different developmental stages of the postnatal rat retina but we showed that for quantification of PAC1 receptor expression, the existence of PAC1 receptor isoforms must be taken into account.…”
Section: Dynamic Changes Of Pac1 Receptor Isoforms Through Postnatal mentioning
confidence: 99%
“…The integration of retinal cells into functional circuits results from temporally overlapping processes (i.e., cell genesis, apoptosis, migration, and synaptogenesis) that are regulated by numerous intrinsic and extrinsic environmental factors. [23][24][25][26][27][28][29] Although the presence of PACAP receptors and their isoforms in the mammalian retina has been described, 15,30 the physiological function of this peptide has not been established, nor has precise quantitative analysis of the PACAP receptor expression in the retina during postnatal development been carried out.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the specifi c PAC1 receptor and VPAC receptors has been confi rmed in the developing mammalian retina, including the retinal progenitor cells [ 44 ]. A shift in PAC1 receptor isoform expression (null, hip, hop1, hiphop1) during development might explain the different roles exerted during differentiation of retinal neural elements [ 45 , 46 ].…”
Section: Distribution Of Pacap Receptors In the Retinamentioning
confidence: 99%
“…However, a complex and diverse set of functions associated with PACAP1-38 has been described in the central nervous system, which encompasses neurogenesis, migration, neural differentiation, and synaptic development. [13][14][15][16] The early appearance in embryonic retina (i.e., PAC1 receptors and PACAP1-38 were detected as early as embryonic days 16 and 19, respectively) 17 and sustained postnatal expression of its receptors 18 indicate that PACAP1-38 very well belongs to a large group of soluble factors that orchestrates retinal development. Functional studies revealed an antimitogenic action of PACAP1-38 on progenitor and postmitotic cells of the newborn retina signaling through both PAC1 and VPAC receptors.…”
mentioning
confidence: 99%